El cuerpo dispuesto: disaffordance identitaria en el deporte universitario: The Able Body: Identity Disaffordance in College Sports (Papeles, 2026)
Introduction: This article analyzes implicit body pedagogies in university sports contexts, conceptualizing obligatory bodily availability as a mechanism of identity disaffordance: the systematic restriction of perceived possibilities for self-conception. The literature has documented phenomena such as the internalization of body ideals, self-objectification, and athletic identity foreclosure; however, these constructs remain theoretically dispersed. The present work proposes that such phenomena constitute manifestations of epistemic appropriation—the process whereby external restrictions become internalized until they cease to be perceived as environmental coercion. Methods: A sequential mixed-methods design was employed, including Likert-type scales administered to 35 participants from university cheerleading teams and semi-structured interviews with selected cases. The scales function as heuristic tools for illustrating theoretically relevant patterns, without claims to psychometric validation or statistical generalization. Quantitative data were analyzed using Radial Analysis (RA), a geometric method that enables visualization of correlations between internalization dimensions and perceived pressure. Results and Discussion: Exploratory patterns illustrate the coexistence of high internalization of body mandates with low perceived external pressure, particularly from peers, confirming the mechanism of epistemic appropriation: when restriction has been successfully internalized, it ceases to appear external. Conclusions: The coherence of the model has direct implications for educational intervention: interventions should focus on environmental redesign that reconfigures the landscape of perceived possibilities, rather than on individualized interventions targeting personal dispositions.
Keywords: Body pedagogy; higher education; disaffordance; epistemic appropriation; university sports; body identity